Increasing the Brand Awareness of SPELL ELC Using a Company Profile Video - Diora Valencia Wicaksono; Henny Putri Saking Wijaya (Kata Kita: Journal of Language, Literature, and Teaching, 2021)
SPELL ELC (Special Programs for English Language & Literacy English Language and Communication) Sidoarjo was established in 2001. Three programs that SPELL ELC has: Academic English, Business English, and Children English. SPELL ELC’s competitor is EF (English First) Sidoarjo. SPELL ELC’s problem is lack of students outside Sidoarjo. Therefore, the best solution to solve this problem is to make a company profile video. A company profile video can reach the customers who live outside Sidoarjo. The solution was made following the theory of Rockman (2017) in order to deliver the information effectively. Survey and interview were conducted to get the USP. Dandy (2020) mentioned that the solution will give four benefits for the company. The benefits are: it helps the customers to know the company’s brand, it can cover the company’s shortcomings, it can be an effective promotional tool, and it can build good images for the company.              Keywords: company profile video, brand awareness, English course